The effects of tax knowledge, tax complexity and tax morale towards tax compliance behavior among salaried group in Malaysia / Yusri Huzaimi Mat Jusoh ...[et al.] - Mat Jusoh, Yusri Huzaimi; Mansor, Farah Ahlami; Abd Razak, Siti Noor Azmawaty; Wan Mohamad Noor, Wan Nurul Basirah (Universiti Teknologi MARA, 2021)
This study examines the relationship between tax knowledge, tax complexity and tax morale with the tax compliance behavior among salaried group in Malaysia. A structured questionnaire was distributed to the private and government sector employees throughout Malaysia. The data analysis from 152 completed responses revealed that tax knowledge, complexity and morale proved to have significant influences on the tax compliance behavior among the salaried group. The findings of this study not only contribute to literature in exploring determinants that encourage voluntary compliance among the taxpayers under the Self-Assessment System (SAS) in Malaysia, they also provide insights to the governing bodies and the tax authorities of the needs to improve the current tax policy and develop strategic movement in improving tax literacy among the taxpayers. This present study, however, has limitations due to the use of closed questionnaires that might not capture further information completely on the understanding of tax regulations and other factors causing non-compliance.